Ethnobotany of Dreams and Dream Interpretations: A study among the Karbis of India - Terangpi, Reena; Phangchopi, Urmika; Teron, Robindra (Ethnobotany Research and Applications, 2015)
The Karbi ethnic group of Northeast India associates many meanings of dreams events with real life. Dream interpretation is an integral part of their traditional religion and healthcare practices. Traditional concept of dreams and the role of 35 plants in dream interpretation are discussed here. We conducted group discussions in 51 randomly selected villages across the plain and hill areas of Karbi Anglong district, Assam, during January 2010 to October 2012. This was followed by interviews of 175 select elders. Karbis recognize three types of dreams: (1) mang jangre, dreams which bear positive correlation with real life; (2) mang kai, dream events which are opposite or unrealistic in real life; and (3) mang phumeng, dreams which do not carry any significant meaning in real life. Certain plants that come in dreams carry important messages which have relevance to the individual and his or her family. Karbis also use many plants and their products for preventing nightmares.